2022
DOI: 10.1063/5.0106642
|View full text |Cite
|
Sign up to set email alerts
|

Electronic state influence on selective bond breaking of core-excited nitrosyl chloride (ClNO)

Abstract: The potential for selective bond breaking of a small molecule was investigated with electron-spectroscopy and electron-ion coincidence experiments on ClNO. The electron spectra were measured upon direct valence photo-ionization and upon resonant core-excitation at the N 1s- and O 1s-edges followed by emission of resonant Auger (RA) electrons. The RA spectra were analyzed with particular emphasis on the assignment of the participator and spectator states. The latter are of special relevance for investigations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…If the subsequently formed valence hole remains sufficiently localised in the proximity of the core hole, site-selective chemical dynamics can occur. Such phenomena have been observed experimentally for a number of photofragmentation processes 6–10 and predicted theoretically for non-dissociative processes such as photoisomerisation. 11…”
Section: Introductionmentioning
confidence: 71%
“…If the subsequently formed valence hole remains sufficiently localised in the proximity of the core hole, site-selective chemical dynamics can occur. Such phenomena have been observed experimentally for a number of photofragmentation processes 6–10 and predicted theoretically for non-dissociative processes such as photoisomerisation. 11…”
Section: Introductionmentioning
confidence: 71%
“…These previous ion–ion coincidence measurements on the ClNO dication [ 27 , 28 ] formed after core excitation at different pre-edge resonances have pointed out the Cl-N bond cleavage with the formation of NO + ions. It has been observed that excitation of similar molecular orbitals of ClNO [ 26 ] (from the N and O atoms) results in different fragmentation patterns [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 93%
“…Double photoionization was studied in a previous experiment mainly dedicated to photoelectron spectroscopy (PES) and X-ray absorption spectroscopy (NEXAFS) in order to deeply characterize the electronic structure of ClNO through a combined experimental and theoretical spectroscopic investigation at the Cl 2p, Cl 2s, N 1s and O 1s edges [ 26 ]. After that, resonant Auger spectra measurements have been taken together with atomic/molecular products ion coincidence detection with resonant Auger electrons [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an experiment would answer questions related to local versus global ionization. Recently, L-edge X-ray absorption has been used to affect product branching. , Such experiments could be used to explore element-specific ionization and intramolecular energy redistribution rates in larger molecules.…”
Section: Future Challengesmentioning
confidence: 99%